Challenges and Attitude of Teachers in Implementing Inclusive Education System in Public Schools - Hina Pathan; Dr. Tarique Bhatti; Jameel Ahmed Qureshi (Review Journal of Social Psychology & Social Works, 2025)
Inclusive education began as special education. Today's global agenda includes inclusive education. Many guidelines and policies are created to execute such laws and rules. Every signatory country must respect the rights of all children, including disabled children. The present study was a descriptive survey. It was done to examine teachers' and parents' attitudes towards inclusive education and school-related issues with its implementation. The study sample includes head teachers, teachers, parents, Taluka Education Officers (TEOs), and District Education Officers (DEOs) from Jamshoro government schools. Data was collected using the 5.0 Likert scale. In data analysis, descriptive statistics were employed. Regarding the first objective, most respondents were aware of inclusive education. The mean score is 3.46 and the SD is 0.806. The second objective showed that government schools struggle to implement inclusive education with a mean score of 3.62 and a standard deviation of 0.694. The third objective of the research found that most respondents were satisfied with educating pupils with mild impairments but not large difficulties. scores average 3.30 with a standard deviation of 0.637. Most respondents agreed with the study's fourth objective: parents prefer mainstream schools over special education institutions. This averages 3.66 and SD is 1.971. Parents also support inclusive education in conventional schools. Today, inclusive education is crucial. Teachers must be trained to conduct inclusive education in regular schools. To allow all special children in rural and urban areas to attend mainstream schools and define their careers, the government should act quickly. The government should help appoint a third-party private instructor in government schools so they can properly educate such children alongside ordinary pupils.